Pengembangan Media Pembelajaran Interaktif Berbasis Android Menggunakan Construct 2 untuk meningkatkan Prestasi Belajar Siswa di SMAN 1 Batukliang Utara - Ahmad Rodi; Ade Kurniawan; Sanapiah Sanapiah (Lembaga Pusat Kegiatan Belajar Masyarakat (PKBM) Tunas Harapan, 2025)
This research aims to determine the validity, practicality and effectiveness of Android-based learning media by utilizing construct 2 to improve student learning achievement at SMAN 1 Batuklaing Utara 2023/2024. The type of research used is development research with the ADDIE model. The research subjects were class XI students at SMAN 1 Batukliang Utara with a sample size of 16 students. Research data was obtained using media and material expert validation questionnaires, teacher and student response questionnaires, as well as pretest and posttest sheets to determine student learning outcomes.The results of expert validation research are very valid, while those for material experts are also very valid. The practical results themselves can be seen from the teacher's response and the student's response, which from the research data shows that they agree and strongly agree. To see the effectiveness of the media, it can be seen from the comparison of student learning outcomes between those who use Android-based learning applications and those who don't, with a difference in the increase in learning outcomes of 13.378%. This research concludes that Android-based learning media is valid, practic and effectiv to improve student learning achievement at SMAN 1 Batuklaing Utara 2023/2024